Effects of N Fertilizer Sources and Tillage Practices on NH3 Volatilization, Grain Yield, and N Use Efficiency of Rice Fields in Central China - Liu, Tianqi; Huang, Jinfeng; Chai, Kaibin; Cao, Cougui; Li, Chengfang (Frontiers in Plant Science, 2018)
Tillage practices and nitrogen (N) sources are important factors affecting rice production. Few studies, however, have examined the interactions between tillage practices and N fertilizer sources on NH3 volatilization, nitrogen use efficiency (NUE), and rice grain yield. This study aimed to investigate the effects of N fertilizer sources (no N fertilizer, inorganic N fertilizer, organic N fertilizer alone, organic N fertilizer plus inorganic N fertilizer, and slow-release N fertilizer plus inorganic N fertilizer) and tillage practices (no-tillage [NT] and conventional intensive tillage [CT]) on NH3 flux, grain yield, and NUE in the rice field of central China. N sources significantly affected NH3 volatilization, as the cumulative volatilization from the treatments of inorganic N fertilizer, organic N fertilizer, organic N fertilizer plus inorganic N fertilizer, slow-release N fertilizer plus inorganic N fertilizer was 4.19, 2.13, 3.42 and 2.23 folds in 2013, and 2.49, 1.68, 2.08 and 1.85 folds in 2014 compared with that under no N fertilizer treatment, respectively. The organic N fertilizer treatment had the lowest grain yield and NUE among all N fertilizer treatments, while slow-release N fertilizer plus inorganic N fertilizer treatment led to relatively higher grain yield and the greatest N use efficiency. Moreover, NT only markedly increased NH3 volatilization from basal fertilizer by 10%–14% in average compared with CT, but had no obvious effects on total volatilization during the whole seasons. Tillage practices had no significant effects on grain yield and NUE. Our study suggested that the combination of slow-release N fertilizer plus inorganic N fertilizer and NT might be a sustainable method for mitigating greenhouse gas and NH3 emissions and improving grain yield and NUE in paddy fields of central China.